2018
DOI: 10.1111/iwj.12920
|View full text |Cite
|
Sign up to set email alerts
|

An aseptically processed, acellular, reticular, allogenic human dermis improves healing in diabetic foot ulcers: A prospective, randomised, controlled, multicentre follow‐up trial

Abstract: Aseptically processed human reticular acellular dermal matrix (HR‐ADM) has been previously shown to improve wound closure in 40 diabetic patients with non‐healing foot ulcers. The study was extended to 40 additional patients (80 in total) to validate and extend the original findings. The entire cohort of 80 patients underwent appropriate offloading and standard of care (SOC) during a 2‐week screening period and, after meeting eligibility criteria, were randomised to receive weekly applications of HR‐ADM plus S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 22 publications
1
44
0
2
Order By: Relevance
“…A significantly higher ulcer healing rate at weeks 16 and 24 was observed of the intervention ADM (I: 70.0% vs C: 49.3%; OR 1.589, P = .044), but this was a per‐protocol analysis . Another study of aseptically processed human reticular ADM (HR‐ADM) of 80 patients assessed the proportion of ulcers closed at 6 weeks compared with a standard care group receiving daily collagen alginate dressing changes . It reported a significantly higher rate of healing (I: 80% vs C: 30%) as well as lower mean time to heal with the intervention, but the study was not blinded and was considered to be at a moderate risk of bias especially as an interim analysis of the same cohort had previously been published …”
Section: Products To Correct Aspects Of Ulcer Biochemistry and Cell Bmentioning
confidence: 99%
“…A significantly higher ulcer healing rate at weeks 16 and 24 was observed of the intervention ADM (I: 70.0% vs C: 49.3%; OR 1.589, P = .044), but this was a per‐protocol analysis . Another study of aseptically processed human reticular ADM (HR‐ADM) of 80 patients assessed the proportion of ulcers closed at 6 weeks compared with a standard care group receiving daily collagen alginate dressing changes . It reported a significantly higher rate of healing (I: 80% vs C: 30%) as well as lower mean time to heal with the intervention, but the study was not blinded and was considered to be at a moderate risk of bias especially as an interim analysis of the same cohort had previously been published …”
Section: Products To Correct Aspects Of Ulcer Biochemistry and Cell Bmentioning
confidence: 99%
“…After reading the full texts, 36 articles were excluded, three of them were duplicate studies [16][17][18], one of them was a conference abstract without available full text [19], while the other one only included 6 patients in the control group [20]. Finally, 9 RCTs were eligible for this metaanalysis [21][22][23][24][25][26][27][28][29]. Table 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…Figure 2. All studies were described as RCTs, of which 5 studies [24,[26][27][28][29] clearly described the method of random sequence generation and 2 studies [26,28] reported allocation concealment. Although the blinding method of participants and personnel were not mentioned in 3 studies [22,23,27], all 9 studies were assessed as having a high risk of performance bias, as AM was easily to be identified during the application by the study staff.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations